Pengaruh Model Problem Based Learning Terhadap Hasil Belajar IPAS Materi Magnet Kelas V SD Negeri 121 Palembang - Haziqah, Iffah; Gunawan Manullang, Jujur; H. M. Lubis, Patricia (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
One of the problems related to students' learning outcomes is the lack of variety in learning models, which causes students to become bored and easily drowsy during the learning process.The purpose of this study is to determine whether the Problem-Based Learning model has an effect on the learning outcomes of fifth-grade students at SD Negeri 121 Palembang. The method used in this research is a Pre-Experimental design with a One-Group Pretest-Posttest type. The population of this study consisted of 84 fifth-grade students at SD Negeri 121 Palembang. From this population, a sample of 56 students was selected using a simple random sampling technique. This study involves two variables: variable X is the Problem-Based Learning model, and variable Y is the science learning outcomes. Data collection techniques used in this study include a pretest, a posttest, and documentation. Based on the results of the t-test calculation, the significance value (2-tailed) for classes V A and V C was 0.000 < 0.025, thus Ho is rejected. This means that Ha is accepted, indicating a significant influence of the Problem-Based Learning model on science learning outcomes in the magnet material among fifth-grade students at SD Negeri 121 Palembang.